Deixis Analysis in Should’ve Said It Song Lyrics by Camila Cabello - Mareta Fauziah; Sri Hartati (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
Deixis is a study to interpret the relationship between situations with words, phrases, and characteristics that are spoken in a sentence. This research focused on deixis in lyrics of Should’ve Said It song by Camila Cabello. The problem of the research is what are the types of deixis found in lyrics of Should’ve Said It song by Camila Cabello. The objective of the research is to find out the types of deixis found in lyrics of Should’ve Said It song by Camila Cabello. The writer used Saeed theory (2016) to analyzed deixis in lyrics of Should’ve Said It song by Camila Cabello. The source of data is Should’ve Said It song and the data is from the lyrics of songs in the Should’ve Said It by Camila Cabello. The writer used a qualitative method as the research method. The result of the research is that there are 52 data, 45 of them are data that show person deixis (I, me, my, you, your, he, it, they), 1 of them are data that show spatial deixis (there), and 6 of them are data that show temporal deixis (now, night).